(untitled) (Acta Scientiarum. Health Sciences, 2014)
The World Health Organization recognizes the medical practices derived from the culture of each country, as Traditional Medicine, but all over the world, there has been no consensus about the denomination of these practices. InBrazil, the Ministry of Health recognizes the use of the following, as Complementary and Integrative Practices (CIP): Acupuncture, Homeopathy, Medicinal Plants/Phytotherapy, Thermal Water/Crenotherapy, Anthroposophic Medicine. Based on the therapies recognized by the Ministry of Health, the Brazilian Federal Council of Dentistry regulated the use of CIP in oral health: Acupuncture, Homeopathy, Phytotherapy, Laser Therapy, Flower Therapy and Hypnosis. This article presents the results of a systematic review about positive and negative evidence of the use of PIC in oral health. We analyzed 91 papers published between 2000 and 2010. Laser therapy and Phytotherapy were the CIP most tested. Laser therapy studies reported more negative results, while the Phytotherapy studies reported more positive results. Papers on Flower Therapy were not included because we found no RCT about this CIP. We found more positive than negative outcomes for the use of CIP in oral health and analysis of the papers showed that only a few authors reported the clinical outcomes. Due to the holistic perspective of CIP, we believe it is possible to show more consistent results of use of these practices in oral health, provided that a broader view (beyond quantitative parameters) is incorporated from the planning to analysis of studies in this area.